Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1076/ceyr.22.4.253.5504
|View full text |Cite
|
Sign up to set email alerts
|

Delayed tear clearance in contact lens associated papillary conjunctivitis

Abstract: Tear clearance in contact lens associated papillary conjunctivitis patients was delayed. We proposed that delayed tear clearance might increase the protein and inflammatory mediator concentrations in the tear film and contribute to the pathogenesis or aggravate the severity of contact lens associated papillary conjunctivitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…82 Contact lens-induced papillary conjunctivitis has been associated with delayed tear clearance, which might increase the protein and inflammatory mediator concentrations in the tear film and contribute to the pathogenesis or aggravate the severity of CLPC. 83 Of interest, MGD is common for patients with CLPC, 84 but no association was found between MGD and delayed tear clearance. 83 It has been proposed that a tear clearance test be incorporated in the eye examination for CL wearers with CLPC, as the treatment modality can be adjusted accordingly.…”
Section: Contact Lens-induced Papillary Conjunctivitismentioning
confidence: 99%
See 2 more Smart Citations
“…82 Contact lens-induced papillary conjunctivitis has been associated with delayed tear clearance, which might increase the protein and inflammatory mediator concentrations in the tear film and contribute to the pathogenesis or aggravate the severity of CLPC. 83 Of interest, MGD is common for patients with CLPC, 84 but no association was found between MGD and delayed tear clearance. 83 It has been proposed that a tear clearance test be incorporated in the eye examination for CL wearers with CLPC, as the treatment modality can be adjusted accordingly.…”
Section: Contact Lens-induced Papillary Conjunctivitismentioning
confidence: 99%
“…83 Of interest, MGD is common for patients with CLPC, 84 but no association was found between MGD and delayed tear clearance. 83 It has been proposed that a tear clearance test be incorporated in the eye examination for CL wearers with CLPC, as the treatment modality can be adjusted accordingly. 83 In cases of decreased tear clearance, nonpreserved steroids may be indicated.…”
Section: Contact Lens-induced Papillary Conjunctivitismentioning
confidence: 99%
See 1 more Smart Citation
“…GPC is associated with the infiltration of basophils, eosinophils, plasma cells, and lymphocytes, which suggest a mixed mast cell-and lymphocyte-mediated process. (Chang & Chang, 2001) …”
Section: Acute Forms Of Allergic Conjunctivitis 331 Seasonal Allergmentioning
confidence: 99%
“…It is suggested that the increase in MMP-9 activity may lead to corneal epithelial disease. Tear clearance is also reduced in subjects with contact lens associated papillary conjunctivitis [33]. Delayed tear clearance may be the best measure for identifying patients with tear film disorders, who may respond to anti-inflammatory therapy [3].…”
Section: Introductionmentioning
confidence: 99%